2012
DOI: 10.1590/s1516-35982012000600022
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between temperament with performance and meat quality of feedlot steers with predominantly Charolais or Nellore breed

Abstract: -The relation between temperament with performance and meat quality was determined in 79 Charolais × Nellore steers kept in feedlot. Temperament was evaluated according to exit velocity, scale composite score and flight distance four times in the finishing phase, along with body weight, intake and feed conversion measures. Cattle were classified as calm, intermediate and excited according to exit velocity measures at the beginning of the trial. Excited cattle presented larger values for composite score and fli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
(35 reference statements)
0
5
1
5
Order By: Relevance
“…Many of the reactions of livestock to humans are attributed to fear (Silveira et al, 2012), which has been shown to be related to factors such as species, breed, sex, age and prior experience (Rushen et al, 2001). During handling, animal welfare can be compromised by a series of factors that include: the training and attitude of operators (Villarroel et al, 2001), the nature of the handling procedures (gentle vs. rough), the temperament of the animals, and the quality of the facilities (Schwartzkopf-Genswein et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the reactions of livestock to humans are attributed to fear (Silveira et al, 2012), which has been shown to be related to factors such as species, breed, sex, age and prior experience (Rushen et al, 2001). During handling, animal welfare can be compromised by a series of factors that include: the training and attitude of operators (Villarroel et al, 2001), the nature of the handling procedures (gentle vs. rough), the temperament of the animals, and the quality of the facilities (Schwartzkopf-Genswein et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, o uso somente da VF para estratificar em grupos de temperamento (calmo, intermediário e reativo), não obteve êxito em distinguir as categorias em FC para zebuínos e taurinos em outro estudo (SILVEIRA et al, 2012).…”
Section: Discussionunclassified
“…Contudo, este estudo não reportou se os testes de temperamento foram eficazes em predizer a maciez ou a FC como realizado por outros estudos que apontaram atuação do sistema proteolítico (GRUBER et al, 2010;HALL et al, 2011;KING et al, 2006;VOISINET et al, 1997). Além disso, os efeitos negativos do temperamento (ou efetividade na predição) sobre características produtivas muitas vezes não estão presentes para maciez (FRANCISCO et al, 2015;SILVEIRA et al, 2012), tornando muitas vezes estudos de correlação inapropriados.…”
Section: Discussionunclassified
See 2 more Smart Citations